Escin’s Multifaceted Therapeutic Profile in Treatment and Post-Treatment of Various Cancers: A Comprehensive Review - Sunnatullo Fazliev; Khurshid Tursunov; Jamoliddin Razzokov; Avez Sharipov (Biomolecules, 2023)
Although modern medicine is advancing at an unprecedented rate, basic challenges in cancer treatment and drug resistance remain. Exploiting natural-product-based drugs is a strategy that has been proven over time to provide diverse and efficient approaches in patient care during treatment and post-treatment periods of various diseases, including cancer. Escin—a plant-derived triterpenoid saponin—is one example of natural products with a broad therapeutic scope. Initially, escin was proven to manifest potent anti-inflammatory and anti-oedematous effects. However, in the last two decades, other novel activities of escin relevant to cancer treatment have been reported. Recent studies demonstrated escin’s efficacy in compositions with other approved drugs to accomplish synergy and increased bioavailability to broaden their apoptotic, anti-metastasis, and anti-angiogenetic effects. Here, we comprehensively discuss and present an overview of escin’s chemistry and bioavailability, and highlight its biological activities against various cancer types. We conclude the review by presenting possible future directions of research involving escin for medical and pharmaceutical applications as well as for basic research.